Ethics of Genetic Engineering and Gene Editing in Humans - Salim Dakhil Rashid; Ahmed Rashid Tubena; Sabah Attwan Kazi; Salim Dakhil Rashid; Ahmed Rashid Tubena; Sabah Attwan Kazi (Jurnal MIPA dan Pembelajarannya, 2026)
The modern biotechnology and medicine have been revolutionized in a short period by genetic engineering and gene editing technologies. Due to the invention of novel and more advanced genome-editing technologies, particularly, CRISPR-Cas9 system, the manipulation of human DNA has become more accurate and efficient than ever before. This group of technologies has enormous potential in curing and perhaps a cure to a variety of hereditary diseases such as Sickle Cell Disease, Cystic Fibrosis and Huntingtons Disease. Gene editing technologies, despite being extremely promising in the field of medical science, are linked with complex ethical, social, and legal concerns of manipulating the human genome. The paper will discuss on the ethical issue of genetic engineering and gene editing, in the case of human beings, using the available academic literature, and ethical debate. The paper covers the main ethical concerns, including the risks of the safety of the technique, the germline editing, the genetic enhancement, the social inequality, and the long-term effects of human genetic modification. The other important element of the research is the importance of ethical governance and international regulation to ensure that using gene editing technologies is responsible. The conclusions made are that although gene editing technologies are potentially very useful in the field of human health and the development of medical science, their implementation requires a strict regulation to avoid their misuse and harm the dignity of human beings. The ethical systems, community engagement and international cooperation have to play a critical role in making sure that the genetic technologies are applied in a responsible and socially beneficial way.